2008
DOI: 10.1177/0269216308095024
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for breathlessness management in patients with lung cancer: a systematic review

Abstract: The aim is to review the published scientific literature for studies evaluating non-pharmacological interventions for breathlessness management in patients with lung cancer. The following selection criteria were used to systematically search the literature: studies were to be published research or systematic reviews; they were to be published in English and from 1990 to 2007; the targeted populations were adult patients with dyspnoea/breathlessness associated with lung cancer; and the study reported on the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…A pharmacological (i.e., opioid treatment) and nonpharmacological (i.e., psychosocial support, relaxation and breathing training) approach is warranted for the alleviation of dyspnea [34]. A systematic review of nonpharmacologic inter ventions in lung cancer has shown a significant impact on breathlessness and related distress [35]. As dyspnea has also been associated with other symptoms, such as pain or anxiety, treating related symptoms may also alleviate dyspnea severity [25].…”
Section: Review Research Reportmentioning
confidence: 99%
“…A pharmacological (i.e., opioid treatment) and nonpharmacological (i.e., psychosocial support, relaxation and breathing training) approach is warranted for the alleviation of dyspnea [34]. A systematic review of nonpharmacologic inter ventions in lung cancer has shown a significant impact on breathlessness and related distress [35]. As dyspnea has also been associated with other symptoms, such as pain or anxiety, treating related symptoms may also alleviate dyspnea severity [25].…”
Section: Review Research Reportmentioning
confidence: 99%
“…Interventions to improve breathing efficiency Breathing retraining has been reported in all reviews to being an effective strategy to manage dyspnoea 9,10]. Breathing retraining techniques with good evidence to support their effectiveness included pursed lip breathing, diaphragmatic breathing, 'blow-as-you-go' and positioning and pacing techniques.…”
Section: Which Nonpharmacological Strategies Are Effective?mentioning
confidence: 99%
“…6 A systematic review on nonpharmacological interventions in lung cancer 13 identified 3 RCTs of nursing multicomponent interventions for dyspnea, including psychosocial support, relaxation, and breathing training, mainly in patients with significant expected survival time (93 months); all showed a significant impact on breathlessness and related distress. 14 An RCT found that facial cooling with a fan also significantly reduced breathlessness. 15 Opening windows if possible, reducing room temperature, eliminating smoke, elevating the head of the bed, and humidifying air can also be helpful.…”
Section: Dyspneamentioning
confidence: 99%